An integrated disaster response information surveillance system. (1st January 2013) - Majagah, Koushby; Haque, Syed
This paper describes the design and development of an integrated disaster response information surveillance (IDRIS) wireless system for use by the emergency medical service (EMS). IDRIS is built on two complimentary models: the architectural model and the computational model. Using front end tablet PCs equipped with wireless technology IDRIS is a real-time data recording, information display, storage, communication and tracking system to be used by the EMS department personnel at disaster sites. With its built-in two complementary models coupled with features to adapt to user behaviour (to suit different conditions), we believe that IDRIS has the potential to be a key component for disaster management strategies, a system for surveillance of diseases and detecting unusual syndromes.